2019
DOI: 10.1016/j.neuron.2019.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Neuronally Enriched RUFY3 Is Required for Caspase-Mediated Axon Degeneration

Abstract: Highlights d Neuronally enriched RUFY3 is cleaved during caspasemediated axon degeneration d RUFY3 functions downstream of or in parallel to caspase-3 in axon degeneration d RUFY3 dephosphorylation upon trophic deprivation appears required for degeneration d RUFY3 knockout causes reduced neuronal cell death and sensory axon misprojections

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
(72 reference statements)
1
14
0
Order By: Relevance
“…Both forms arise by alternative splicing of the RUFY3 pre-mRNA. The short form had been shown to be particularly abundant in the brain, and to play roles in neuronal polarity and the regulation of axon specification, growth and degeneration (Hertz et al, 2019;Honda et al, 2017;Mori et al, 2007;Wei et al, 2014). The existence, distribution and function of the long form had not been previously documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both forms arise by alternative splicing of the RUFY3 pre-mRNA. The short form had been shown to be particularly abundant in the brain, and to play roles in neuronal polarity and the regulation of axon specification, growth and degeneration (Hertz et al, 2019;Honda et al, 2017;Mori et al, 2007;Wei et al, 2014). The existence, distribution and function of the long form had not been previously documented.…”
Section: Discussionmentioning
confidence: 99%
“…1d). The shorter RUFY3.2 is the only RUFY3 spliceform characterized to date; previous studies showed that it plays roles in neuronal polarity and axon formation and degeneration (Hertz et al, 2019;Honda et al, 2017;Mori et al, 2007;Wei et al, 2014), and in cancer cell migration, invasion and metastasis (Men et al, 2019;Wang et al, 2015;Xie et al, 2017;Zhu et al, 2019). Protein and mRNA expression databases (e.g., https://www.proteinatlas.org/) indicate that RUFY3 is expressed in all cells and tissues, Keren-Kaplan et al…”
Section: Identification Of Rufy3 and Rufy4 As Arl8 Effectorsmentioning
confidence: 99%
“…Olfactory dysfunction occurs in 90% of AD cases and is correlated with elevated rufy3 expression in glomerular and mitral layers of the olfactory bulb ( Zelaya et al, 2015 ). RUFY3 is cleaved by caspase 3 and critically required for caspase-mediated degeneration of tropomyosin receptor kinase A positive sensory axons in vitro and in vivo ( Hertz et al, 2019 ; Figure 4C ). Removal of neuronally enriched RUFY3 is able to block caspase 3-dependent apoptosis, while dephosphorylation of RUFY3 at residue S34 appears required for its degradation ( Hertz et al, 2019 ).…”
Section: Rufy3mentioning
confidence: 99%
“…RUFY3 is cleaved by caspase 3 and critically required for caspase-mediated degeneration of tropomyosin receptor kinase A positive sensory axons in vitro and in vivo ( Hertz et al, 2019 ; Figure 4C ). Removal of neuronally enriched RUFY3 is able to block caspase 3-dependent apoptosis, while dephosphorylation of RUFY3 at residue S34 appears required for its degradation ( Hertz et al, 2019 ). Analysis of rufy3 -deficient mice supports a second distinct function for RUFY3 in neuronal growth and polarity, since mutant embryos show defects in axonal projection patterns.…”
Section: Rufy3mentioning
confidence: 99%
See 1 more Smart Citation